Short Story Text Writing Learning by Creative-Productive Model based on Verbal Creativity of Eleventh Graders of VHS (Universitas Negeri Semarang, 2019)
Short story writing skill is needed by students to produce a short story based on their creative imagination. Suitable learning is done by using a creative, productive model based on students’ verbal creativities. This research aims to find out the effectiveness of short story writing skill by using a creative-productive model based on eleventh graders of VHS verbal creativities. This quasi-experimental research used the instrument of collecting data such as a test of short story writing, verbal creativity test, behavioral observation, photographs, and interview. Normality tests used Kolmogorov-Smirnov. Homogeneity test used Levense test. Hypothesis test used paired sample t-test. Final data analysis used a t-test to find out the comparison of the learning effectiveness based on verbal creativities. The findings showed an average score of high verbal creativity students was 87.40, moderate 81.05, and the lowest average of 76.6. It proved the learning was effective to be implemented for high verbal creativity students. This research contributes to enrich research development dealing with the educational field and to enrich knowledge in learning writing short story at schools.